Validation of MIPAS and SCIAMACHY Data by Ground-Based Spectroscopy at Kiruna, Sweden, and Izana, Tenerife Island (AOID-191) - Blumenstock, Thomas; Mikuteit, Sabine; Griesfeller, Alexandra; Hase, Frank; Kopp, Gerhard; Kramer, Isabell; Schneider, Matthias; Fischer, Herbert; Gil, Manuel; Moreta, J.R.; Navarro Coma, M.; Raffalski, Uwe; et al. (2004)
Ergebnisse von MIPAS und SCIAMACHY werden mit Bodenbeobachtungen verglichen